2013
DOI: 10.1590/s1677-5538.ibju.2013.04.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Analgesic Efficacy of Penile Block, Caudal Block and Intravenous Paracetamol for Circumcision: A prospective Randomized Study

Abstract: Purpose: To evaluate the postoperative analgesic efficacy of penile block, caudal block and intravenous paracetamol administration following circumcision. Materials and Methods:In this prospective randomized study a total of 159 patients underwent circumcision under general anesthesia at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…Thus, pain control was much better in group B neonates whereas neonates in group A experienced much pain immediately after the circumcision. These observations disagree with a previous study from Turkey where there was no significant difference in the mean pain scores after 1 h, although an intravenous acetaminophen injection was used and the cohort of patients studied was from 1 to 7 years [19]. The findings in this study may be related to the onset of action and duration of action as well as the route of administration of these agents.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, pain control was much better in group B neonates whereas neonates in group A experienced much pain immediately after the circumcision. These observations disagree with a previous study from Turkey where there was no significant difference in the mean pain scores after 1 h, although an intravenous acetaminophen injection was used and the cohort of patients studied was from 1 to 7 years [19]. The findings in this study may be related to the onset of action and duration of action as well as the route of administration of these agents.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with a prior Cochrane systematic review (2008) involving 4 RCTs (N = 336), as the study also failed to reveal any difference in the efficacy or need for rescue analgesia between CB and PB (RR = 1.25, 95% CI = 0.64 to 2.44, p = 0.52) [22]. A RCT of 104 patients by Haliloglu et al (2013) reported a higherpain score in children postoperatively following PB at 30 minutes but not at 60 minutes (30 minutes: p < 0.001 and at 60 minutes: p = 0.189) [1]. These results suggest any difference in analgesia after PB and CB wanes quickly after the first half hour of administration.…”
Section: Discussionsupporting
confidence: 89%
“…Male circumcision is the most common pediatric surgical procedure performed globally [1] [2]. Worldwide regional prevalence varies significantly due to social, cultural, and religious influences [3].…”
Section: Introductionmentioning
confidence: 99%
“…[12] To our knowledge, there are few studies comparing validated pain scale scores and only one prior study comparing procedural time. [12][13][14][15] In addition, prior studies comparing analgesic efficacy consist of small retrospective case series. [12][13][14][15][16][17][18][19][20] The purpose of this study was to compare intraoperative and 1-hour postoperative outcomes of caudal blocks vs. DPNBs in pediatric patients undergoing outpatient penile surgeries.…”
Section: Introductionmentioning
confidence: 99%